Driving Behaviour of Elderly Drivers in Malaysia - Rosli, Naida; Ambak, Kamarudin; Shahidan, Nurfatin Nadiah; Abdul Sukor, Nur Sabahiah; @Liew Shyuan Yei, Sharifah Osman (International Journal of Integrated Engineering, 2020)
Aging of population has increased in most developed countries. In year 2030, the aging population in Malaysia will reach 15% of the population. This situation contributes to the increasing number of older drivers on the road. Thus, it is important to identify the needs and safety aspects of driving among the elderly. The objective of this study was to determine the characteristics of basic driving skills among older drivers and their driving behavior. An instrument adapted from Driver Behavior Questionnaire (DBQ) was used to collect survey data. A total of 240 car drivers aged 50 years and above completed the questionnaire. For observation data, 150 respondents were chosen in order to observe their driving skills especially at intersections and parking areas. A Correlation analysis and Chi-Square test were performed to study the relationship between their age and driving skills. Results showed majority of the respondents demonstrated that they had knowledge of basic driving skills. Observation study at parking areas showed that selection of parking space, in and out parking skills, time taken to park, vehicle position and number of passengers were significant towards gender. While, observation at intersections showed that only vehicle distance was significant towards gender. Three variables (the older drivers being comfortable driving on the left lane, older drivers were often honked during driving and older drivers being slow responding to hazards such as pedestrians at the crossing) were correlated and significant at p<0.05 . This study recommended providing older drivers with priority lanes, special parking areas and car sticker tagging â€œolder driverâ€ in addition to supervising their licenses, conducting driving class sessions and undergoing medical examination for them.